STRUKTUR DAN FUNGSI SOSIAL KEPERCAYAAN RAKYAT UNGKAPAN LARANGAN MASA HAMIL, MELAHIRKAN DAN MASA KANAK-KANAK DI DESA TUNGKAL III KECAMATAN TUNGKAL ILIR KABUPATEN TANJUNG JABUNG BARAT PROVINSI JAMBI - Sari, Winda Novita; WS, Hasanuddin; Nst., Muhammad Ismail (Universitas Negeri Padang, 2018)
This thesis aims to describe the structure and function of social beliefs of the people expression prohibition of pregnancy, child birth and childhood in Village Tungkal III districtsTungkal Ilir districtTanjung Jabung Barat Province Jambi. The data source of this research was obtained from one main informant and three supporting informants. The place of this research is in Village Tungkal III districts Tungkal Ilir districtTanjung Jabung Barat ProvinceJambi.Data collection techniques in this study were conducted using observation, interview, and record techniques. Based on the results of the study concluded the following points. First, the structure of people's confidence in the prohibition of pregnancy, childbirth, and childhood in Village Tungkal III districts Tungkal Ilir district Tanjung Jabung Barat Province Jambi consists of 2 structures, namely two-part structure and three-part structure. Meanwhile, for the social function of people's trust in the expression of prohibition in Village Tungkal III districts Tungkal Ilir district Tanjung Jabung Barat Province Jambi is to strengthen the emotions of belief, as a system of imaginary projections, educate, prohibit.Â Keywords: foklore, structure, social function, expression of prohibition